Henry IV of Germany, 1056-1106 - Robinson, I. S. (Ian Stuart), 1947 February 11- (Cambridge University Press, 1999)
This is the first book in English devoted to the German king and emperor Henry IV (1056-1106), whose reign was one of the most momentous in German history and a turning-point in the history of the medieval empire (the kingdoms of Germany, Italy and Burgundy). The reign was marked by continuous rebellions and fluctuating fortune. Earlier monarchs had also witnessed conflict between crown and aristocracy, but Henry IV's reign differed in that his conflicts could never be definitively resolved either by negotiation or by war. During the 1070s the young king gained a lasting reputation for tyranny, while his assertion of the crown's traditional rights over the imperial church aroused papal opposition. The alliance between the German princes and the papacy haunted Henry IV for the rest of his life. He meanwhile, by turns opportunist and compromiser, dedicated himself at all times to preserving the traditional rights of the monarchy.